Expansion of trading opportunities to the year 2000 for Asia-Pacific developing countries (UN New YorkUS, 1995)
Sees the Uruguay Round as beneficial to the Asia-Pacific developing countries in the future though the Intellectual Property Rights clause might cause erosion of competitiveness in European, North American and Japanese markets. Suggests ways in which countries could expand their exports and attract foreign direct investment. Provides country reports for countries where economic progress has been built upon rapid expansion of exports.
DC